Social Internet of Vehicles decentralized collaborative caching method - MA HUAHONG; XIE PING; ZHANG GAOYUAN; XING LING; FAN YIZHENG; JI BAOFENG; WANG BAIBING; ZHENG GUOQIANG; JIN JICHONG; WU HONGHAI (2023)
The invention discloses a social Internet of Vehicles decentralized cooperative caching method, which comprises the following steps: taking a road side unit and an intelligent vehicle in the social Internet of Vehicles as caching nodes, adopting a DQN model to construct a decentralized cooperative caching model, setting the state of the DQN model as a caching and requesting state, and setting the action as a content request processing action, meanwhile, a corresponding reward function is designed, the cache model is trained through federal learning, and then each vehicle determines a current cache strategy according to the cache model. According to the invention, the road side units and the intelligent vehicles in the social networking of vehicles are used as cache nodes, and the DQN model is adopted to construct the decentralized cooperative cache model, so that decentralized cooperative cache is realized, and the cache capability of the social networking of vehicles is improved. 本发明公开了一种社交车联网去中心化协作缓存方法，将社交车